2019
DOI: 10.1155/2019/7096912
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Prevents Contrast-Induced Nephropathy via Modulating Tubular Cell Mitophagy and Suppressing Mitochondrial Fragmentation, CCL2/CCR2-Mediated Inflammation, and Intestinal Injury

Abstract: Contrast-induced nephropathy (CIN) is a leading cause of hospital-acquired acute kidney injury (AKI), but detailed pathogenesis and effectual remedy remain elusive. Here, we tested the hypothesis that contrast media (CM) impaired mitochondrial quality control (MQC) in tubules, including mitochondrial fragmentation and mitophagy, induced systemic inflammation, and intestinal injury. Since we previously demonstrated that the natural antioxidant 2,3,5,6-tetramethylpyrazine (TMP) can be a protectant against CIN, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
(72 reference statements)
2
32
0
Order By: Relevance
“…In rats, TMP prevents CIN kidney injury in vivo by reversing the associated pathological processes. Mechanistically, TMP efficiently reversed the CM-induced activation of the CCL2/CCR2 pathway, ameliorated renal oxidative stress and aberrant mitochondrial dynamics by restoring the alterations in Drp1 and Mfn2 expression, modulated mitophagy in tubular cells, and suppressed the expression of autophagy genes, including those encoding LC3B, Beclin-1, and p62 protein (Gong et al, 2019). In a cisplatin (a chemotherapeutic drug)-induced model of AKI, treatment of proximal tubule-specific autophagy-deficient mice with cisplatin led to severe mitochondrial damage and promoted ROS production, DNA damage, and p53 activation.…”
Section: Nephrotoxic Akimentioning
confidence: 96%
See 1 more Smart Citation
“…In rats, TMP prevents CIN kidney injury in vivo by reversing the associated pathological processes. Mechanistically, TMP efficiently reversed the CM-induced activation of the CCL2/CCR2 pathway, ameliorated renal oxidative stress and aberrant mitochondrial dynamics by restoring the alterations in Drp1 and Mfn2 expression, modulated mitophagy in tubular cells, and suppressed the expression of autophagy genes, including those encoding LC3B, Beclin-1, and p62 protein (Gong et al, 2019). In a cisplatin (a chemotherapeutic drug)-induced model of AKI, treatment of proximal tubule-specific autophagy-deficient mice with cisplatin led to severe mitochondrial damage and promoted ROS production, DNA damage, and p53 activation.…”
Section: Nephrotoxic Akimentioning
confidence: 96%
“…Thus far, studies on the role of autophagy in kidney proximal tubules have often yielded contradictory or unconvincing results (Periyasamy-Thandavan et al, 2008;Inoue et al, 2010;Kimura et al, 2011;Jiang et al, 2012;Liu et al, 2012;Livingston and Dong, 2014;Takabatake et al, 2014;Choi, 2019). We speculate that the reasons for such conflicting data include (1) the use of different autophagy agonists and inhibitors, which are not entirely specific and may have some unknown targets (Kimura et al, 2011;Livingston and Dong, 2014), and when administered at different doses, these autophagy agonists and inhibitors may exhibit different thresholds for autophagy intervention; (2) the differences in the function and degree of damage in different proximal tubule segments (for example, in the AKI mouse model, IRI epithelial cell damage is most apparent in the S3 segment of the proximal tubule, while mitochondrial density is the highest in the S1 segment, and the oxidative burst primarily occurs in the S2 segment; Bao et al, 2017;Gong et al, 2019; therefore, the role of autophagy genes in different proximal tubule segments may differ; one study reported that Atg5 deletion in the whole proximal tubule exacerbates kidney injury in AKI; Takahashi et al, 2012); and (3) the differences in the sex and strains of the experimental animals. Therefore, it is better to choose the same strain for breeding conditional knockout mice (such as the breeding of Cre/loxp recombinases or the insertion of fluorescent reporter in transgenic mice).…”
Section: Nephrotoxic Akimentioning
confidence: 99%
“…Similar to cisplatin, TUNEL-positivity was observed in tubular epithelium in 3–7 days after administration of these drugs [ 66 , 78 ]. Other toxic AKIs induced by heavy metal (i.e., mercury) exposure [ 47 , 60 ], nanomaterial consumption [ 79 , 80 ], or associated with rhabdomyolysis [ 81 ] or contrast-induced nephropathy [ 54 , 82 , 83 ] resulted in TUNEL-positivity in tubular epithelium within hours and up to the first week after exposure. Sepsis-induced AKI is multifactorial and includes microcirculatory dysfunction and renal inflammation.…”
Section: Tunel Applicationsmentioning
confidence: 99%
“…Methods of TUNEL quantification vary. In the majority of reports, TUNEL-positive cells/nuclei are quantified as the percent of total cells/nuclei [ 83 , 116 , 117 ]. This seems the right thing to do, although the number of TUNEL-positive cells likely do not correspond exactly to the number of dead cells.…”
Section: Tunel Quantification and Colocalization Techniquesmentioning
confidence: 99%
“…The latest work by Gong et al verified the activation of mitophagy in CI-induced AKI in rats. The natural anti-oxidant tetramethylpyrazine suppressed ROS production, mitophagy, mitochondrial fragmentation, and renal tubular cell apoptosis in CI-induced AKI [126]. In addition, Mitophagy was also noticed in renal tubules in FA-induced AKI in rats [127], and in diatrizoic acid (DA)-induced renal tubular cell injury [128], but the precise role and regulation of mitophagy in these settings remain unknown.…”
Section: Mitophagy In Other Types Of Akimentioning
confidence: 99%